THE CURRENT STATE AND THE PERSPECTIVES OF ROBOTICS DEVELOPMENT: IN THE GLOBE AND RUSSIA - N. N. Bondareva (Модернизация, инновация, развитие, 2016)
In the article the methodological bases for the new criteria of goods and services efficiency and standards in a new cyber environment, and also the reasons and consequences of the robotic goods and services demands' transformation are defined. The newest era of the mass cyber development and hybridization as the following robotization stage is predicted, the analysis of the new mass commercialization challenges and threats of its breakthrough researches is carried out. The global environment influence on the level of corporate robotization and replacement of a non-hybrid environment by the totally hybrid environment are given on the example of the countries pioneers of the forced technological development (Japan, the USA, South Korea, and Germany). The definitions and the existing robots' classifications of three generations are revealed, taking into the account its main criteria robots' so called self-training ability.The methodological criteria and requirements to the leading countries' competitiveness in a new cyber environment in "the sixth technological shift era", including the military, social, political and economic stability, the defensive potential in the new hybrid and contactless cyber wars, are described.The comparative analysis of the well-known forecasts is conducted, including 'The Future of Employment is carried out: How Susceptible Are Jobs to Computerization" by Karl Frey and Michael Osborn, 'The Future of Jobs, 2025: Working Side-By-Side with Robots" from "Forrester Research" the forecast of the World Economic Forum (WEF) of'The Future of Jobs" from 2016 and "Robotic Nation" of Marshall Brian, for the period till 2025 about the mass robotization effects, including the influence of robotization on the global employment.The target approach analysis is carried out, as well as the progressive methodological approaches on the governmental and corporate levels are described. The value of the efficient implementation criteria of the Revolutions of Robots Program in Japan is defined (key quantitative planned targets till 2020, and the five areas for the scientific researches concentration). The analyzed best experience is expedient to be applied in the Russian Federation, including the strategic robotic development plan in Japan, aimed at the transformation of the non-robotic systems into the fully robotic systems and the forced mass robotization.The complex analysis of the cross-disciplinary links, valued for the scientific breaks through, which define the global technological development, is given.The analytical list of the revealed robotization challenges and threats to governments, business, safety, health, private life, freedom of consciousness and the person al will is provided. The new business purposes, roles and tasks in the robotization an era and the governmental functions are revealed, and the global needs' and demands' transformation forecast is given.It is supposed that a robot's competitiveness will depend on its existing in-building technological ability level and/or the new technological environmental level for the following generation of the robotic line embedding, taking into an account the field robotic efficiency criteria. The importance of rationalization and multifunctional, dual purpose robotic abilities is emphasized.The conditions of the new hybrid environment connected with robotization are revealed: The quantitative analysis of the main global androids projects is provided. The author's innovations in the article are meaningful for the decisions making persons in the field of robotization.